THU0379 Efficacy and Safety of Anti-TNF Alpha in NON Infectious Inflammatory Uveitis: Preliminary Results of A French Multicenter Registry of 162 Patients. (10th June 2014) - Vallet, H.; Seve, P.; Riviere, S.; Perard, L.; Bielefeld, P.; Abad, S.; Rigolet, A.; Perlat, A.; Fain, O.; Bienvenu, B.; Le Hoang, T.; Sene, D.; et al.
Abstract : Background: Etiologies of non infectious inflammatory uveitis are multiple. Their prognosis can be severe and may lead to blindness. Anti-TNF alpha are used for several years in refractory inflammatory uveitis but few data on large studies have been reported. Objectives: The aim of this study is to report on the efficacy and the safety of anti-TNF alpha in inflammatory uveitis. Methods: We performed a retrospective multicenter study of main characteristics and outcomes of 162 patients with inflammatory uveitis treated with anti-TNF alpha. Results: The median of age was 30 years [19-40] and with 59% of women. Uveitis were mainly bilateral (82%) and chronic (87%). Panuveitis, macular oedema and retinal vasculitis were observed in 62, 54 and 35% of cases, respectively. Main etiologies of uveitis included juvenile idiopathic arthritis (25%), Behçet's disease (24%), spondylarthropathies (12%), and sarcoidosis (6%). Patients were treated by infliximab in 58%, adalimumab in 39.5% or etanercept in 2.5%. The median of follow up was 27 months [8-55]. Ninety three percent of patients were complete or partial responders to anti-TNF alpha therapy. No significant difference was found relative to efficacy between infliximab and adalimumab. Anti-TNF alpha had a significant corticosteroid sparing effect (daily prednisolone dose of 20mg at time of introduction of anti-TNF alpha vs 10mg and 5mg at 6 and 12 months, respectively; p<0, 0001). The median time for clinical improvement was 67 days [43-103]. Adverse events were reported in 27% of patients, mainly with infliximab. They included mainly infections (8%) and hypersensitivity reactions (7%). Serious side effects were reported in 10% of cases and required treatment interruption in all cases. Conclusions: These preliminary results showed that TNF alpha inhibitors are highly efficient in severe and refractory non infectious inflammatory uveitis. Infliximab and adalimumab had the same efficacy profile but infliximab was associated with more frequent and more serious side effects. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.6013